Taxonomic revision of the genus Tetraglochin (Rosaceae, Rosoideae) and morphometric analysis of its species - Cialdella, Ana M.; Pometti, Carolina L. (Phytotaxa, 2017)
Tetraglochin is a small genus distributed along the Andes from Perú to southern Argentina and central Chile, belonging to the family Rosaceae. Systematic studies in Tetraglochin are scarce, and circumscription of some members of this genus is controversial. In order to evaluate the degree of morphological differentiation between the species of this genus, we performed morphometric analyses using multivariate methods (non parametric ANOVA, phenetic analysis and canonical discriminant analysis) including those specimens with intermediate characteristics between T. alata and T. ameghinoi. The phenogram obtained showed two principal clusters; this picture suggested a clear grouping of the specimens of T. alata, T. ameghinoi, T. aff. alata and T. andina. In the canonical discriminant analysis five groups were found and in general terms all individuals of T. alata, T. aff. alata and T. ameghinoi were grouped together. When multivariate analyses were applied almost all specimens could be correctly assigned to its species. However, specimens of T. alata, T. aff. alata and T. ameghinoi , were not well discriminated. Following recent phylogenetic results on the genus, and morphometric analyses perfomed herein for the first time, we present an updated taxonomic revision of Tetraglochin, based on exomorphological, vegetative and reproductive characters, including a key to identify species and varieties, their associated synonymy, full descriptions, geographical distribution and illustrations. As result, a new combination, T. alata var. ameghinoi is proposed, T. alata var. patagonica is reduced to synonymy of T. alata var. alata, and T. paucijugata and T. tragacantha are reduced to synonymy of T. cristata. Lectotypes for Margyricarpus acanthocarpus, Tetraglochin acanthocarpa var. lasiocarpa, var. dasycarpa, var. macropoda and var. lejocarpa are designated. One species, Tetraglochin buxifolia is excluded from the genus.